Cost‐of‐illness of psoriasis – results of a German cross‐sectional study. (26th September 2017) - Jungen, D.; Augustin, M.; Langenbruch, A.; Zander, N.; Reich, K.; Strömer, K.; Thaci, D.; Purwins, S.; Radtke, M.; Gutknecht, M.
Abstract: Background: Though psoriasis poses a substantial chronic socio‐economic burden, few studies have addressed the economic impact in Germany. Objectives: The objective was to evaluate the annual costs of psoriasis in Germany from the societal perspective. Methods: A cross‐sectional study was performed in randomly selected German dermatology practices and clinics in 2013/2014 using standardized questionnaires of illness‐related costs. Costs were grouped by perspective and category as well as analysed by sex and age. Group differences were tested by non‐parametric tests. Results: Complete data were obtained from 1158 patients in 132 centres. Annual average costs for patients with psoriasis: total costs € 5543 ± € 8044, systemic treatment costs (paid by the statutory health insurances [SHI]) € 3733 ± € 7322, out‐of‐pocket costs € 224 ± € 406, total SHI costs € 4940 ± € 7533, direct costs € 5164 ± € 7581 and indirect costs € 379 ± € 2087. Significant higher costs in male and significant lower costs in 65+‐year‐old patients were found. Conclusions: Psoriasis induces a considerable economic burden. Between 2003 and 2014, costs have markedly shifted from hospital, out‐of‐pocket and indirect costs towards systemic drug costs.